Quantitative Comparison of the Vascular Structure of Macular Neovascularizations Between Swept-Source and Spectral-Domain Optical Coherence Tomography Angiography - Faatz H (Dove Medical Press, 2020)
Henrik Faatz,1 Kai Rothaus,1 Martin Ziegler,1 Marius Book,1 Claudia Lommatzsch,1,2 Georg Spital,1 Matthias Gutfleisch,1 Daniel Pauleikhoff,1,3,4 Albrecht Lommatzsch1,3,4 1Department of Ophthalmology, St. Franziskus Hospital, Münster, Germany; 2Department of Ophthalmology, University of Lübeck, Lübeck, Germany; 3Department of Ophthalmology, University of Essen–Duisburg, Essen, Germany; 4Achim Wessing Institute for Imaging in Ophthalmology, University Hospital Essen, Essen, GermanyCorrespondence: Henrik Faatz Tel +49 251 935 2711Fax +49 251 935 2749Email henrik.faatz@augen-franziskus.dePurpose: The aim of this study was to ascertain and quantify the differences between swept-source (SS) and spectral-domain (SD) optical coherence tomography angiography (OCTA) imaging of macular neovascularizations (MNV) in neovascular age-related macular degeneration (nAMD).Patients and Methods: SD-OCTA (RTVue Avanti) and SS-OCTA (PLEX® Elite 9000) were performed in 37 patients with MNV in nAMD. The MNV was delineated and the data were processed via ImageJ. The parameters MNV area, nodes per area, fractal dimension (FD), and flow density were analyzed using MatLab.Results: There was close agreement between the two devices regarding MNV area (ICCc 0.977, ICCa 0.977, R2 0.977), but only slight agreement regarding nodes per area (ICCa 0.008, ICCc 0.548, R2 0.51), FD (ICCa 0.425, ICCc 0.846, R2 0.96), and flow density (ICCa 0.451, ICCc 0.656, R2 0.65). The difference between the two devices was insignificant for MNV area (type 1: p=0.328; type 2: p=0.426; type 3: p=0.615), but significant for nodes per area (type 1: p=0.002; type 2: p=0.00001; type 3: p=0.003), FD (type 1: p< 0.00001; type 2: p< 0.00001; type 3: p=0.015) and flow density (type 1: p=0.0004; type 2: p=0.004; type 3: p=0.052).Conclusion: MNV area is closely comparable between devices using SS-OCTA and SD-OCTA imaging. However, the two methods differ significantly in their precise assessment of the vascular morphology (FD, flow density, nodes per area). Therefore, results obtained using different devices are not comparable and should not be amalgamated in clinical trials.Keywords: choroidal neovascularization, neovascular age-related macular degeneration, optical coherence tomography angiography